Consumer Minimalism - Wilson, Anne V; Bellezza, Silvia (Journal of Consumer Research, 2022)
Abstract Minimalism in consumption can be expressed in various forms, such as monochromatic home design, wardrobe capsules, tiny home living, and decluttering. This research offers a unified understanding of the variegated displays of minimalism by establishing a conceptual definition of consumer minimalism and developing the 12-item Minimalist Consumer Scale to measure the construct. Three distinct dimensions of consumer minimalism are identified: number of possessions (reflecting the ownership of few possessions), sparse aesthetic (reflecting the preference for simple and uncomplicated designs), and mindfully curated consumption (reflecting the thoughtful selection of possessions). A series of studies, using samples from a variety of populations (N = 3,735) demonstrates the validity and reliability of the tridimensional Minimalist Consumer Scale, situates the measure conceptually and empirically within a broader nomological network of related constructs (e.g., voluntary simplicity, frugality, green values, materialism), and documents the scale’s ability to predict relevant consumer preferences and behaviors.